A hybrid photoelectrocatalytic/photoelectro-Fenton treatment of Indigo Carmine in acidic aqueous solution using TiO2 nanotube arrays as photoanode - Oriol, Roger (2019)
This article reports the synthesis of TiO2 nanotube arrays (TiO2 NTs), grown by Ti anodization, and their use as photoanode in a hybrid photelectrocatalytic (PEC)/photoelectro-Fenton (PEF) treatment of Indigo Carmine solutions in sulfate medium at pH 3.0. The anode was combined with an air-diffusion cathode that ensured continuous H2O2 electrogeneration. Comparative trials by electrochemical oxidation with electrogenerated H2O2 (EO-H2O2), electro-Fenton (EF) and PEF with Pt anode were made. The photoanode was stable operating up to 3 mA cm−2 with irradiation from a 36-W UV LED lamp, showing photoelectroactivity from an anodic potential (Ean) of +0.20 V, as determined by cyclic voltammetry. At 3 mA cm−2, color removal by EO-H2O2 with Pt and PEC with TiO2 NTs was very slow, being much faster in EF, PEF and PEC/PEF due to main role of [rad]OH formed from Fenton's reaction upon addition of Fe2+. The absorbance and dye concentration decays agreed with a pseudo-first-order kinetics, yielding a slightly lower rate constant for decolorization because of the formation of colored products. The mineralization ability increased as: EO-H2O2 ≪ EF ≪ PEF < PEC/PEF. The holes photogenerated at the TiO2 NTs surface had higher oxidation ability than [rad]OH formed at the Pt surface from water discharge. In PEC/PEF, a slower mineralization was found at 2 mA cm−2, although the final mineralization percentage was similar to that attained at 3 mA cm−2. Both, SO4 2− and NH4 + ions were released during the treatments, along with isatin-5-sulfonic and formic acids as main products.